Risk Factors for a High Comprehensive Complication Index after Splenectomy Plus Pericardial Devascularization for Portal Hypertension - Zhang, Yafei; Lu, Hongwei; Ji, Hong; Li, Yiming (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Mathematical integration of all complications from the Clavien–Dindo classification into one number called the comprehensive complication index provides a novel method to capture morbidity. This objective of this study was to compare the evaluations of complications between the novel comprehensive complication index and Clavien–Dindo classification for portal hypertension patients who underwent splenectomy plus pericardial devascularization. Materials and Methods: Patients treated with either splenectomy plus simplified pericardial devascularization or splenectomy plus traditional pericardial devascularization were included retrospectively. Correlation and logistic regression analyses of the postoperative hospital stay and total hospitalization expense were compared between the comprehensive complication index and Clavien–Dindo classification. The cumulative sum-comprehensive complication index was generated and compared between operation types. Results: The Child–Pugh classification at admission, spleen thickness, and intraoperative blood loss were risk factors for high comprehensive complication index. Comprehensive complication index showed a stronger relationship with the postoperative hospital stay and total hospitalization expense than the Clavien–Dindo classification. Logistic regression analysis of the postoperative hospital stay demonstrated that the R2 values for the comprehensive complication index and Clavien–Dindo classification were 0.15 and 0.14, respectively. The cumulative sum-comprehensive complication index graph showed a steady dynamic decrease in the cumulative sum score for the individual operation type, with splenectomy plus simplified pericardial devascularization revealing a more notable decrease than splenectomy plus traditional pericardial devascularization. Conclusions: Comprehensive complication index is an excellent method to assess postoperative morbidity in portal hypertension patients. The cumulative sum-comprehensive complication index chart can better dynamically monitor and compare different operation types. Splenectomy plus simplified pericardial devascularization is better than splenectomy plus traditional pericardial devascularization at decreasing cumulative sum-comprehensive complication index.